Judicial restraint in America how the ageless wisdom of the federal courts was invented - Lee, Evan Tsen. (New York ; Oxford : Oxford University Press, 2011)
This traces the cultural, social, and intellectual forces that shaped the contours of judicial restraint from the time of John Marshall, through the Warren Court, and up to the present.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 10, 2011).
Keywords: United States. -- Supreme Court -- History; Judicial process -- United States -- History